2009
DOI: 10.1007/s11816-009-0087-6
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of rice mutants susceptible to Magnaporthe oryzae

Abstract: To identify genes involved in rice Pi5-mediated disease resistance to Magnaporthe oryzae, we compared the proteomes of the RIL260 rice strain carrying the Pi5 resistance gene with its susceptible mutants M5465 and M7023. Proteins were extracted from the leaf tissues of both RIL260 and the mutant lines at 0, 24, and 48 h after M. oryzae inoculation and separated by two-dimensional polyacrylamide gel electrophoresis (2-DE). Matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 60 publications
(54 reference statements)
1
8
0
Order By: Relevance
“…Transgenic plants overexpressing OsWRKY13 , OsWRKY31 , OsWRKY45 , and OsWRKY53 showed enhanced resistance to M. oryzae , indicating their important roles in rice blast resistance [17][21]. Large-scale approaches have also been used to study rice early response to M. oryzae , including EST sequencing [22], robust-long serial analysis of gene expression [23], proteomics [24], [25], and microarrays [26]. A number of genes potentially involved in rice blast resistance were identified from these studies.…”
Section: Introductionmentioning
confidence: 99%
“…Transgenic plants overexpressing OsWRKY13 , OsWRKY31 , OsWRKY45 , and OsWRKY53 showed enhanced resistance to M. oryzae , indicating their important roles in rice blast resistance [17][21]. Large-scale approaches have also been used to study rice early response to M. oryzae , including EST sequencing [22], robust-long serial analysis of gene expression [23], proteomics [24], [25], and microarrays [26]. A number of genes potentially involved in rice blast resistance were identified from these studies.…”
Section: Introductionmentioning
confidence: 99%
“…In the comparative proteome study of rice strains carrying the Pi5 R gene with susceptible mutants against challenge of M. oryzae , eight proteins were differentially regulated between resistant and susceptible plants. Among them, an abundance of three proteins were found to be increased in resistance cultivar, including a triosephosphate isomerase, a 2,3-bisphosphoglycerate-independent phosphoglycerate mutase, and an unknown protein, while five downregulated proteins included a fructokinase I, a GST, an atpB of chloroplast ATP synthase, an aminopeptidase N, and an unidentified protein (Ryu et al, 2009). A comparative proteome study was performed between two incompatible interactions ( M. oryzae vs. ZTS rice leaf sheaths expressing whole plant-specific resistance [WPSR] and resistant rice ZTR (carrying Pi-zt ) and one compatible interaction ( M. oryzae vs. ZTS rice leaf sheaths in which WPSR was suppressed by ABA).…”
Section: Key Proteome Responses Underlying Rice Resistance To M Oryzaementioning
confidence: 99%
“…As a major fungal pathogen, the interaction between Magnaporthe oryzae inducing rice blast disease and rice plants was reported by Jung et al (2005), Kim et al (2009), and Ryu et al (2009). In the previous study though secretome analysis in rice supension-cultured cells treated with M. oryzae or its elicitor, 21 differential protein spots regulated by fungus and its elicitor were identified and it was revealed that most of them are involved in defense response against pathogens (Kim et al 2009).…”
Section: Biotic Plant Proteomicsmentioning
confidence: 99%
“…In the previous study though secretome analysis in rice supension-cultured cells treated with M. oryzae or its elicitor, 21 differential protein spots regulated by fungus and its elicitor were identified and it was revealed that most of them are involved in defense response against pathogens (Kim et al 2009). Furthermore, proteomics analysis using resistant line and susceptible line to M. oryzae identified 4 metabolism-associated proteins such as fructokinase, triosephosphate isomerase and 2 defense proteins, GST and aminopeptidase N, indicating that proteomics analysis is a useful approach for identifying novel proteins related in pathogen resistance (Ryu et al 2009). Meanwhile, this proteomics approach has been also used to investigate physiological interaction between plant and beneficial microorganisms promoting plant growth as well as plant response to pathogen.…”
Section: Biotic Plant Proteomicsmentioning
confidence: 99%